Dosimetric comparison of dose distributions in episcleral plaque brachytherapy - Acar, Hilal; Ozbay, Imre (Elsevier İreland Ltd., 2015)
Purpose/Objective: Brachytherapy of intraocular tumors with 125I eye plaques has become a successful treatment modality and a viable alternat ive to enucleation. Plaque Simulator (PS) is an eye plaque treatment planning system (TPS) that uses TG-43 dosimetry. We aimed to verify the performance of the PS routinely used to plan patients having intraocular tumors. Materials and Methods: Relative dose distributions, including central axis depth dose and off axis dose profiles of Collaborative Ocular Melanoma Study (COMS) plaques with 14, 16, 18 and 20 mm in diameter, loaded with model I25.S16 seeds were measured using 1x1x1 mm3 Thermo Luminesans Dosimetry (TLD) cubes and computed using MCNP5 Monte Carlo code and Plaque Simulator (PS) TPS. Measurements and calculations were compared by normalizing 5 mm distance at the central axis of the plaque i.e COMS point.
Keywords: Dosimetric; Episcleral Plaque Brachytherapy; Dose Distributions